2000
DOI: 10.1002/1521-3803(20001001)44:5<339::aid-food339>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soaking process on nutritional quality and protein solubility of some legume seeds

Abstract: Legume seeds (soy bean, lupin and bean seeds) were soaked in 0.5% sodium bicarbonate in attempt to evaluate their nutritional quality and protein solubility index. Soaking process led to an increase in the hydration coefficient, seed weight, total protein, ash, fat, fiber, while non protein nitrogen, total carbohydrates, starch, stachyose, raffinose, reducing sugars, and minerals (except Na) were decreased. All antinutritional factors such as phytic acid, tannin, trypsin inhibitor and hemagglutinin activity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 18 publications
1
26
7
Order By: Relevance
“…Hydrothermal cooking before water extraction improves foaming and emulsifying properties (Wang & Johnson, 2001) and thermal treatments of the grain (extrusion, microwave) cause changes of chemical composition and nutritive quality (Zilic, Bozovic, Savic, MladenovicDrinic, & Bekric, 2002) affecting the techno-functional properties (Lampart-Szczapa et al, 2006). Soaking seeds in water or in sodium salts (bicarbonate, chloride) solutions or treatment with carbohydrases reduces the amount of oligosaccharides (El-Adawy, Rahma, El-Bedawey, & Sobihah, 2000; Wanasundara & Shahidi, 1997), and improves the functional properties of proteins (El-Adawy et al, 2000;Inyang & Ekanem, 1996). Soaking seeds in sodium bisulfite solutions and in acidic media remove phenolics compounds (Bau, Mohtadi-Nia, Mejean, & Debry, 1983;Kilara, Humbert, & Sosulski, 1972).…”
Section: Oilseed Processing Into Protein Productsmentioning
confidence: 74%
See 1 more Smart Citation
“…Hydrothermal cooking before water extraction improves foaming and emulsifying properties (Wang & Johnson, 2001) and thermal treatments of the grain (extrusion, microwave) cause changes of chemical composition and nutritive quality (Zilic, Bozovic, Savic, MladenovicDrinic, & Bekric, 2002) affecting the techno-functional properties (Lampart-Szczapa et al, 2006). Soaking seeds in water or in sodium salts (bicarbonate, chloride) solutions or treatment with carbohydrases reduces the amount of oligosaccharides (El-Adawy, Rahma, El-Bedawey, & Sobihah, 2000; Wanasundara & Shahidi, 1997), and improves the functional properties of proteins (El-Adawy et al, 2000;Inyang & Ekanem, 1996). Soaking seeds in sodium bisulfite solutions and in acidic media remove phenolics compounds (Bau, Mohtadi-Nia, Mejean, & Debry, 1983;Kilara, Humbert, & Sosulski, 1972).…”
Section: Oilseed Processing Into Protein Productsmentioning
confidence: 74%
“…Chemical modifications are commonly used in studies performed to characterize the relationships between structure, stability and functional properties of isolates (Dua, Mahajan, & Mahajan, 1996;El-Adawy et al, 2000;Gruener & Ismond, 1997). Most studies performed with food proteins are based on the derivatization of the groups e-amino of lysine residues.…”
Section: Modification Of Oilseed Proteins For Improving Their Functiomentioning
confidence: 89%
“…The highest yield was obtained from Mash 1-1 and the lowest yield from PU-19 (Table 1). Previous studies have reported that yield of protein isolates from mung bean flour was 13.0e19.0% (El-Adawy, Rahma, El-Bedawy, & Sobihah, 2000;Rahma, Dudek, Mothes, Gornitz, & Schwenke, 2000). Thus, present findings were comparable with reported values.…”
Section: Resultsmentioning
confidence: 98%
“…After soaking 17 different pea varieties for 18 h and then boiling them for 20 min, trypsin inhibitor content was reduced in all of the varieties by 42-92% (TIU/mg DM), with an average reduction of 78% (TIU/mg DM) (Morrison et al, 2007). Other studies demonstrate variability in protease inhibitor activity after utilizing different time and temperature combinations, depending on the species, cultivar and treatment method (Alonso et al, 1998;El-Adawy, Rahma, El-Bedawy, & Sobihah, 1999;Marquez & Alonso, 1999).…”
Section: Methods For Reducing Protease Inhibitory Compounds In Pulse mentioning
confidence: 99%